Bringing Local Foods to the Farm Bill - Pingree, Chellie (Maine Policy Review, 2011)
U.S. House Representative Chellie Pingree addresses the importance of revising the Federal Farm Bill to provide greater support to small, local farms if Maine and the nation are to have a sustainable food system..